Aplicação de processos MAG curto-circuito convencional e controlado na soldagem de dutos de aço carbono - Costa, Thonson Ferreira (2011)
The demand for versatile and high-productivity welding processes is a continuing need, especially for pipelines, which represent the basis for different fluid flows. Thus, research in pipe welding, using MAG process with controlled short-circuit transfer, has become a trend in the search for high quality welds, since the current control improves metal transfer, providing stability to the welding process and weld pool. In this context, this paper aims to establish operational limits and advantages of MAG processes with short-circuit transfer for conventional and controlled (STT, RMD and CMT) modes, during single-pass welding of small-diameter pipes with thin wall and using both ascending and descending progression and taking into account the criteria of acceptability and weld-bead geometry. Therefore, a set of parameters from each process, the wire-feed speed and welding techniques (such as, the attack angle and torch oscillation) were varied following different operational designs, trying to keep the same amount of material deposited per length of weld. The welds were carried out in carbon steel pipes ABNT 1020 with 2½\" nominal diameter and 5.5-mm thickness, grooved in accordance with the recommendations of AWS D10.12 (V joint with 75º include angle). Also, ER 70S-6 wire with 1.2-mm diameter was used with Ar+25%CO2, as shielding gas. The results showed that the upward progression has greater penetration, while descending is more suitable for higher travel speeds. It was also observed that the conventional short-circuit mode presented reasonable results for both upward and downward progression, resulting in a uniform operational envelope, whereas STT and RMD processes have larger operational envelope in downward progression. On the other hand, STT process presented a more robust operational envelope with larger working-range for voltage setup for all levels of wire-feed speed. Finally, CMT process presents a more robust operational envelope for upward progression with considerable lower voltage values, which explains the overall lower heat input.